THE EXPANSION AND OPTIMIZATION OF RETAIL BANKING SERVICES IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
This paper examines contemporary global trends in retail banking services and evaluates their possible effects on the banking industry in Uzbekistan. The study explores digital transformation, the rise of fintech, customer-centric service models, and regulatory reforms as primary drivers reshaping retail banking worldwide. It further assesses how these changes might impact Uzbekistan's banking sector, offering strategic recommendations to leverage emerging opportunities and address potential challenges.